Postprivatization Corporate Governance: the Role of Ownership Structure and Investor Protection - Narjess Boubakri; Jean-Claude Cosset; Omrane Guedhami (Fondazione Eni Enrico Mattei (FEEM), 2003)
We investigate the role of ownership structure and investor protection in postprivatization corporate governance. We find that the government relinquishes control over time, mainly to the benefit of local institutions and foreign investors. We also show that private ownership tends to concentrate over time. In addition to firm-level variables, investor protection, political and social stability explain the cross-firm differences in ownership concentration. We find that the positive effect of ownership concentration on firm performance matters more in countries with weak investor protection and that private domestic ownership leads to higher performance.
Keywords: G32; G38; 330; Corporate governance; privatization; performance; Corporate Governance; Privatisierung; Eigentümerstruktur; Anlegerschutz; Schwellenländer